The effect of social cognition and risk tolerance on marine pilots' safety behaviour. Issue 1 (2nd January 2021) - Xi, Yongtao; Zhang, Qingxiao; Hu, Shenping; Yang, Zaili; Fu, Shanshan
ABSTRACT: The safety psychology of marine pilots affects their operational pilotage behaviour. This paper aims to analyze how social cognition (i.e. attitude and perception) and personality traits (i.e. risk tolerance) of marine pilots affect their safety behaviour through Structural Equation Modeling (SEM). Primary sample data is obtained by a survey from the pilots of the Shanghai port, with total of 306 collected results. The results indicate the safety behaviour of marine pilots concerning that 1) the hazardous attitude has a significant positive effect; 2) risk tolerance has an indirect influence; and 3) risk perception has both direct and indirect impacts. Based on this finding, the managerial implications for pilotage safety include that 1) the reduction of the level of hazardous attitude of marine pilots can improve the safety behaviour of marine pilots, 2) the level of risk perception can increase through psychological training and safety education, which is beneficial to comprise the possible effect of increased ability by pilot skill training on risk tolerance.